Utilization of compressible hydrogels as electrolyte materials for supercapacitor applications. Issue 17 (12th April 2023) - Jain, Amrita; Ziai, Yasamin; Bochenek, Kamil; Manippady, Sai Rashmi; Pierini, Filippo; Michalska, Monika
Abstract : (a) Detailed procedure of the fabrication of each layer. (b) FE-SEM image of the hydrogel. (c) Mechanical properties of the hydrogel with and without addition of C-NPs. (d) Macroscopic demonstration of the hydrogel and mechanical flexibility. Abstract : Utilization of CoO@Co3 O4 - x -Ag ( x denotes 1, 3, and 5 wt% of Ag) nanocomposites as supercapacitor electrodes is the main aim of this study. A new low-temperature wet chemical approach is proposed to modify the commercial cobalt oxide material with silver nanoparticle (NP) balls of size 1–5 nm. The structure and morphology of the as-prepared nanocomposites were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and N2 adsorption–desorption measurements. Hydrogels known to be soft but stable structures were used here as perfect carriers for conductive nanoparticles such as carbons. Furthermore, hydrogels with a large amount of water in their network can give more flexibility to the system. Fabrication of an electrochemical cell can be achieved by combining these materials with a layer-by-layer structure. The performance characteristics of the cells were examined by electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), and galvanostatic charge discharge (GCD). Cobalt oxide modified with 5 wt% Ag gave the best supercapacitor results, and the cell offers a specific capacitance of ∼38 mF cm −2 in two-electrode configurations.